The Mental Lexicon of Elementary School Students in Indonesian EFL Context - Mardiana, Rizdika; Haryono, Rudi (Nusantara Science and Technology Proceedings)
Learning English in primary schools needs to be supported by books and reading materials that are appropriate for the child's age level. If children's reading materials are adjusted to their age, children will not have difficulty in understanding their reading text. The purpose of this study was to find out the number and types of English words that were produced by elementary school-age children as the first step to map children's mental lexicon as a reference for the teacher to choose reading text in learning English at school or home. It was descriptive and qualitative research in which data was taken from elementary school students' English writing. The results show that the 1st grade of elementary school students produced 45 words in three different topics namely animals, drinks, and activities. The fourth grade of elementary school students produced 130 until 600 words in writing a fiction story and their total vocabulary were 636 words. The fifth grade of elementary school students produced 1400 words in some different topics namely daily routine, pets, hobbies, like, and dislike. In conclusion, the higher level of education the children have, the more words they produce. The influence of Indonesian and Arabic in students’ composition indicates that Indonesian and Arabic are active languages ??that they use so that it can significantly affect the production of the English they are learning. Verbs that they produce imply that they can understand general and specific concepts possessed by each word.